Educational Leadership Based on Social Capital for Improving Quality of Private Secondary School - Suwadi (Jurnal Pendidikan Islam, 2017)
This study aims to explain the leadership pattern of social capital based education for the quality improvement of private schools. The research is conducted at a private Junior Secondary Level with a qualitative naturalistic approach. This location is in Sleman District. The subject consists of selected cases purposively. The research procedure is carried out by four steps and methods of obtaining the data through observation, in-depth interviews, and documentation. Data analysis was carried out by the inductive model while the level of trust result of the research was undertaken by fulfilling criteria of credibility, transferability, dependability, and conformability. The research findings are as follows. First, the concept of leadership of social capital based education rests on the ability of principals to influence school resources to achieve goals through an integrated pattern of trust dimensions, reciprocal relationships, and networking. Second, school quality can be improved through a) school leadership in recognizing social capital, b) school leadership in utilizing social capital, c) school leadership in functioning social capital. Third, the utilization of social capital based on leadership in private schools in the form of a) bridging stakeholder aspirations both initiated by schools and stakeholders; b) bonding stakeholder relations with schools; c) following up or responding to stakeholder resources in-school programs as a perspective new leadership at school.